2016
DOI: 10.1039/c6tx00161k
|View full text |Cite
|
Sign up to set email alerts
|

Guarana (Paullinia cupana Mart.) attenuates methylmercury-induced toxicity in Caenorhabditis elegans

Abstract: The influence of routine guarana (Paullinia cupana) consumption on apparent tolerance to mercury intoxication has been proposed. The present study investigated this hypothesis in Caenorhabditis elegans, a suitable experimental model for studies in toxicology. Wild type (WT) and skn-1 (ok2315) worm strains were pretreated with guarana ethanolic extract (GEE) from larvae 1 (L1) to L4 stage and then exposed for 6 hours to methylmercury (MeHg). The analyses included evaluation of GEE’s effects on lethality, develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Thus, the use of endemic plants is a more realistic alternative for these populations to protect themselves against MeHg-induced neurotoxicity. In recent years, many efforts have been devoted to the analysis of plants used by vulnerable populations in developing countries, such as India or Brazil [20,73,74,75,76,77]. Thus, this work contributes to the need to find alternatives for vulnerable populations exposed to MeHg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the use of endemic plants is a more realistic alternative for these populations to protect themselves against MeHg-induced neurotoxicity. In recent years, many efforts have been devoted to the analysis of plants used by vulnerable populations in developing countries, such as India or Brazil [20,73,74,75,76,77]. Thus, this work contributes to the need to find alternatives for vulnerable populations exposed to MeHg.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was hypothesized that the consumption of Amazonian fruits would protect exposed populations, reducing the accumulation of mercury in humans [19]. Despite of that, studies with Amazonian fruits and MeHg intoxication are relatively scarce, being mainly limited to fruits such as guaraná, maná-cubiu, burití and açaí [20,21,22,23,24]. Although guaraná ( Paullinia cupana , Mart.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This eventually decreased the intracellular MeHg concentration mediated by the increased concentrations of MRP1 and MRP2 ABC transporters (4042). Similarly, the Skn1 transcription factor, which is the homolog of the mammalian Nrf2 in Caenorhabditis elegans , is involved in the resistance of this nematode worm to MeHg, and the ethanolic extract of the guarana plant was shown to protect skn-1 -mutated nematodes against MeHg (43). MeHg also increased Nrf2 activation by the downregulation of the Fyn kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we investigated the protective properties of antioxidant compounds, β‐selenoamines, against TAA‐induced oxidative damage. Several studies have shown that antioxidant therapies attenuate the tissue damage caused by oxidative stress . In this regard, we designed our study following previous results from our lab showing that β‐selenoamines presented significant antioxidant properties in vitro and in a Caenorhabditis elegans model …”
Section: Discussionmentioning
confidence: 99%